Genetic Variability and Heritability of in vitro Chrysanthemum on Various Combination of Plant Growth Regulators - Muh Farid BDR (Agrotech Journal, 2018)
Heritability is a measure that describes the magnitude of a genetic influence on a character rather than an environmental factor. The higher the heritability value of a character, the higher the genetic variability. The aim of the study was to know the interaction between the combination of growth regulators and chrysanthemum varieties that gave the best chrysanthemum growth in vitro and analyzed the heritability of various chrysanthemum characters. The research was carried out at the In vitro Laboratory of Agronomy Department, Faculty of Agriculture, Hasanuddin University, Makassar from May to September 2016. The study used a separate plot design in the group. The main plot was a combination of growth regulator consisting of 200 ml Coconut Water, 0.5 ppm BAP + Coconut Water 100 ml, BAP 1 ppm + Coconut Water 100 ml, 2,4-D 0.5 ppm + Coconut Water 200 ml, 2,4-D 0.5 ppm + BAP 0.5 ppm + Coconut Water 100 ml, 2,4-D 0.5 ppm + BAP 1 ppm + Coconut Water 100 ml. The subplots included 8 varieties of chrysanthemum (Fiji Pink, Marimar, Pasopati, Salzieta, Solida Pelangi, Limeron, Arosuka Pelangi, Yellow Tumohon). The basic media used was MS medium. The results showed that adding 200 ml young coconut to the culture media gave the best in-vitro chrysanthemum growth in terms of shoot and root formation, shoot count, root number, and shoot height in all chrysanthemum varieties; as well as all observed characters have high heritability and genetic variability